Lung functions and quality of life in flour millworkers - a cross sectional study. - REEMA RELKAR-JOSHI,; MANISHA RATHI,; TUSHAR J.PALEKAR, (International Journal of Pharma and Bio Sciences, 2016)
Occupational health represents a dynamic equilibrium or adjustment between the industrial workers and their occupational health. Occupational lung diseases mostly occur due to effect of dust depending upon the concentration of dust particles in the air, the fineness of the dust, health condition of worker exposure to environment. The study helped, to find out the effectiveness of dust exposure in lung function among flour mill workers and their quality of life. To find out lung function in flour mill workers, type of pathology and quality of life in flour mill workers. Methodology: Total 150 subjects were included in the study which was divided into 2 groups. Group A was having 75 flour mill workers and Group B was having 75 normal healthy subjects who were not exposed to flour mill dust. Assessment for BMI, chest expansion, PFT were taken (FVC, FEV1, FEV1/FVC,PEFR, FEF25-75%) and Quality of life questionnaire SF-36 was filled. 95% confidence interval was considered to be significant. Chest expansion was significantly reduced at both the levels in Group A than Group B (p<0.001 )There was significant reduction in FVC, FEV 1, PEFR, FEF25-75% values in comparison with control group except in FEV1/FVC ratio. PFT in flour mill workers showed that 27 workers were had an obstructive disorder, 23 workers had a restrictive disorder and 25 were normal, whereas PFT in the control group showed only 9 workers were had a obstructive disorder and 66 showed normal PFT. There is significant reduction seen in the quality of life among flour mill workers as compare to control except in Domain V Emotional well-being . There was inverse correlation found between years of exposure of flour dust and lung functions. Whereas quality of life was not correlated with the number of years exposure in flour mill workers. Flour mill workers shows significant reduction in lung functions as well as quality of life except in emotional well-being.